ETHNIC RELATIONS IN DAGHESTAN: SPECIAL FEATURES AND CURRENT PROBLEMS - BUTTAEVA, Asiat (CENTRAL ASIA AND THE CAUCASUS, 2012)
In recent years, problems relating to the state and development dynamics of ethnic relations, which have an effect on the sociopolitical and moral-psychological atmosphere in Russia, are becoming an increasingly frequent target of study. Resolving sociopolitical problems is particularly important in the context of the current instability in the Northern Caucasus. For more than one decade now, ethnic relations have been playing an important role in the fate of the peoples living in the Poly cultural expanse of the Northern Caucasus. If historical development is viewed through the growing internal diversity of the social relations system as a whole, it can be seen that ethnic development and ethnic differentiation have always been the primary vector for determining the nature and direction of this development.1 Many thinkers and politicians have tried to penetrate to the core of ethnic relations in search of optimal forms and ways to build them. Scientific discussions have been held on important problems relating to a substantive understanding of the culture of interrelations among the ethnicities (peoples) of Russia. Russian researchers continue to discuss issues relating to ethnic relations today; resolving them is extremely important for understanding Russia’s future civilizational development. The interest of Russian intellectuals and politicians in ethnic relations in Russia (as well as in the North Caucasian republics) rose dramatically after the collapse of the Soviet Union and the Westernizing reforms of the Yeltsin period. When the Soviet Union fell apart, the Northern Caucasus turned into a zone of conflict and instability, which was largely related to the struggle of the region’s peoples for independence. As we know, the Russian-Chechen conflict, which destabilized the entire Caucasus, was the acutest. The corrupt way in which state property was divvied up caused further degradation and inefficiency of the Russian economy and also hampered the development of competition and the market economy, which led to flagrant social inequality. The political sphere was taken over by functionaries from the old system, bureaucrats, oligarchs, and downright criminals, who, despite the struggle among these different groups for power, were closely interrelated.2 This development of events led to ethnic problems that affected the essential matters of statehood and federalism, as well as the social self-awareness of Russian citizens, going beyond the interests of specialists and becoming part of the public consciousness.